Decision making : cognitive models and explanations - Ranyard, Rob; Crozier, W. Ray, 1945-; Svenson, Ola (Frontiers of cognitive science., 1997)
This book offers an exciting new collection of recent research on the actual processes that humans use when making decisions in their everyday lives and in business situations.